Aplikasi Model DeLone and McLean untuk Mengukur Keberhasilan Sistem Informasi Penelitian dan Pengabdian Masyarakat di Universitas Brawijaya - Puspitasari, Tri; Kusumawati, Andriani; Sujarwoto, Sujarwoto (JSINBIS (Jurnal Sistem Informasi Bisnis), 2020)
Aplication of DeLone and Mclean's Model (2003) renewed is very appropriate measuring the success of information system. This study aims to identify key success factors in the net benefits of information system used for managing research and community services at Brawijaya University. We applied DeLone and McLean model for identifying the key factors of the information system. Data were collected through survey involved 250 University Brawijaya lecturers. The results of the Structural Equation Modeling (SEM) analysis showed the net benefits of the information system were determined by the satisfaction and intention of the lecturers to use the information system, meaning that the more satisfied the lecturers were with the information system and the greater their intention to use the existing information system, the net benefit received would be bigger. Among the three factors that determine the satisfaction and intention of lecturers to use the system, the quality of the system has a greater influence than the quality of information and services.